193 The Human Neocortex Demonstrates Projectors and Receivers of Influence: A Consideration in Neuromodulation Therapy. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Entz, Laszlo; Toth, Emilia; Keller, Corey J.; Groppe, David; Megevand, Pierre; Fabo, Daniel; Ulbert, Istvan; Eross, Lorand G.; Mehta, Ashesh
Abstract: INTRODUCTION: The role of cortical connectivity in brain function and pathology is increasingly being recognized. While in vivo magnetic resonance imaging studies have provided important insights into anatomical and functional connectivity, these methodologies are limited in their ability to detect electrophysiological activity and the causal relationships that underlie effective connectivity. METHODS: Here, we describe results of cortico-cortical evoked potential (CCEP) mapping using single pulse electrical stimulation in 25 patients undergoing seizure monitoring with subdural electrode arrays. Mapping was performed by stimulating adjacent electrode pairs and recording CCEPs from the remainder of the array. To facilitate group analysis, electrode sites were assigned to Brodmann areas (BAs) based upon transformation to MNI space. Early onset ictal electrodes and non-ictal electrodes were separated and differences in network properties were assessed. RESULTS: CCEPs reliably revealed functional networks and showed an inverse relationship to distance between sites. Connections were frequently directional with relative dominance of incoming or outgoing connections. The most consistent connections were seen as outgoing from motor cortex, BA6 to BA9, somatosensory cortex, anterior cingulate cortex and Broca area. Network topology revealed motor, somatosensory and premotor cortices along with BA9 and BA10 and language areas to serve as hubs for cortical connections. BA20 and BA39 demonstrated the most consistent dominance of outgoing connections, while BA5, BA7, auditory cortex and anterior cingulum tended to receive more incoming connections. Pathological networks involving the ictal onset zone demonstrated greater local and lesser long-range connectivity as well as a tendency to receive more than projected. CONCLUSION: A large-scale intersubject connectivity map shows directionality of cortical connections. Hub areas, areas projecting causal influence and receiver areas are identified. These basic differences may help to identify pathological networks.